'Twas the night before Christmas - Kirk, Daniel; Moore, Clement Clarke, 1779-1863. (New York : Abrams Books for Young Readers, 2015)
An adaptation of the poem about a familiar Christmas Eve visitor.
School Library Journal, October 2015.
Publisher's Weekly, September 2015.
4.1
K-3
AD940L
Keywords: Christmas poetry; Children's poetry; Christmas -- Poetry; Christmas -- Poetry; Children's poetry; Christmas -- Poetry; Santa Claus -- Poetry; Poetry